Optimizing Customer Relationships: A Case Study of CRM Practices at Puma Outlet in Ahmedabad city of Gujarat - Harsh Ravani; Dhruval Bhalani; Jignesh Vidani (International Journal of Integrated Science and Technology, 2024)
Effective client Relationship Management (CRM) techniques are essential in the current competitive retail environment to maintain client loyalty and stimulate corporate expansion. This study aims to investigate and assess customer relationship management (CRM) techniques used in Puma shops. It seeks to provide insights into the impact of these tactics on customer relationships and the overall success of the organisation. The study uses a qualitative methodology, conducting in-depth interviews with branch managers in various geographical areas and market conditions. The findings indicate that common customer relationship management (CRM) tactics include the use of technology to handle data, personalised marketing efforts, and the implementation of loyalty programmes. The positives that have been identified include the efficient utilisation of customer data and the proactive interaction with customers. On the other hand, the limitations are related to the integration of CRM practices across all points of contact and the maintenance of data quality.This study makes theoretical contributions by connecting CRM theories with actual implementations, emphasising the changing role of technology and human interaction in enhancing CRM effectiveness. This study enhances the current CRM literature by offering in-depth understanding of a particular retail environment, opening up opportunities for further investigation into upcoming technologies and CRM tactics across other retail sectors.Ultimately, the results emphasise the crucial significance of CRM methods in cultivating client connections and promoting retail achievements in the digital age. Retail managers may use these observations to continually enhance their CRM strategies, while researchers are urged to explore more into the ever-changing environment of CRM to further enhance retail efficiency and consumer involvement.